The ocean of mirth : reading Hāsyārṇava-prahasanaṃ of Jagadēśvara Bhaṭṭāchārya - a political satire for all times /: reading Hāsyārṇava-prahasanaṃ of Jagadēśvara Bhaṭṭāchārya - a political satire for all times. (2019) - Sharma, Jyotirmaya
No abstract available